İZAHA DAVET MÜESSESESİ: KURAMSAL ÇERÇEVE, UYGULAMA VE DEĞERLENDİRME - (:unkn) unknown (My University, 2018)
İzaha davet müessesesi, Vergi Usul Kanunu’nun mülga 370. mad-desinin 6728 sayılı Kanun ile “İzaha Davet” başlıklı yeniden düzenleme-si neticesinde Türk vergi literatürüne girmiş bir kavramdır. Müesseseninuygulaması ise, 482 sıra numaralı Vergi Usul Kanunu Genel Tebliğiuyarınca 01.09.2017 tarihi itibarıyla başlamıştır. İzaha davet, vergininziyaa uğradığına delalet emarelerin bulunduğuna dair yetkili mercilertarafından yapılmış ön tespitler neticesinde, aynı merciler tarafındanmükelleflerden açıklama istenmesidir. Çalışmamızda izaha davet mües-sesesinin amacı, niteliği, kapsamı ve şekli, ön tespitin niteliği, izaha da-veti yapacak ve değerlendirecek merci, izaha davet yapılacaklar ve izahadavetin olumlu ve olumsuz yanları ortaya konulmaya çalışılacaktır.

The invitation to explain is a concept entered into the Turkish tax literature as a result of the reorganization of Article 370 of the Tax Pro- cedure Law with the title of "Invitation to Explain" with the Law No. 6728. Implementation of the institution has started as of 01.09.2017 in accordance with the General Communique of the Tax Procedure Law numbered 482. The invitation to explain is to ask the taxpayers for clari- fication on the basis of the preliminary determinations made by the competent authorities regarding the presence of evidence about lossof tax. In this study, we will try to present the goal, character, content and wise, character of preliminary detection, the authority to invite and eva- luate, taxpayers who will be invited and positive and negative aspects of the institution of invitation to explain.
INSTITUTION OF INVITATION TO EXPLAIN: THEORETICAL FRAMEWORK, PRACTICE AND EVALUATION
Keywords: Hukuk